Literature Review Nursing Care Effort To Prevent Parasitic Diseases - Reqgi First Trasia (Genius Journal, 2020)
Intoduction: Infectious diseases are diseases that can be transmitted or passed from a person who is sick to people who are healthy or have not been exposed to the infectious disease. Transmission of the disease can occur either through intermediaries or directly. Standard precautions should always be taken applied in all health service facilities in providing health services safe for all patients and reduces the risk of further infection. There are so many work accident in hospital due to low intention in prevention of transmission. Objective: The aim of this article is to review the nursing care effort to prevent parasitic disease. Method: Writing a study of this scientific articles is made using the reading method model or literacy, analyzing and tracing various references. Result: This review found that both nursing students and nursing professional personnel must be able to improve obedience in the use of personal protective equipment and also always apply the 6 principles of cleanliness in wash hands both before taking action and after taking action with patients, in order to prevent disease transmission. Conclusion: As nurses must maintain body stamina and body health by increasing the body's immune system not easy to catch the disease.